2014
DOI: 10.1186/1746-4811-10-19
|View full text |Cite
|
Sign up to set email alerts
|

AGROBEST: an efficient Agrobacterium-mediated transient expression method for versatile gene function analyses in Arabidopsis seedlings

Abstract: BackgroundTransient gene expression via Agrobacterium-mediated DNA transfer offers a simple and fast method to analyze transgene functions. Although Arabidopsis is the most-studied model plant with powerful genetic and genomic resources, achieving highly efficient and consistent transient expression for gene function analysis in Arabidopsis remains challenging.ResultsWe developed a highly efficient and robust Agrobacterium-mediated transient expression system, named AGROBEST (Agrobacterium-mediated enhanced se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
156
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(160 citation statements)
references
References 58 publications
3
156
0
1
Order By: Relevance
“…The AGROBEST (Agrobacterium-mediated enhanced seedling transformation) method achieves high transient transformation efficiency in whole seedlings, allowing gain-of-function studies, by using a pH-buffered medium supplemented with AB salts and glucose. It has been shown that transient expression of GUS or LUC of Col-0 or efr-1 seedlings was significantly enhanced when AGROBEST was used during A. tumefaciens inoculation (Wu et al, 2014b). Similar to what was observed for agroinfiltration in adult leaves (Wroblewski et al, 2005), C58C1(pTiB6S3DT-DNA, pCH32) achieves higher transient transformation efficiency than the wild type C58 virulent strain or the C58-derived disarmed strain GV3101(pMP90) in A. thaliana seedlings (Wu et al, 2014b).…”
Section: Transient Transformation In Seedlingsmentioning
confidence: 78%
See 2 more Smart Citations
“…The AGROBEST (Agrobacterium-mediated enhanced seedling transformation) method achieves high transient transformation efficiency in whole seedlings, allowing gain-of-function studies, by using a pH-buffered medium supplemented with AB salts and glucose. It has been shown that transient expression of GUS or LUC of Col-0 or efr-1 seedlings was significantly enhanced when AGROBEST was used during A. tumefaciens inoculation (Wu et al, 2014b). Similar to what was observed for agroinfiltration in adult leaves (Wroblewski et al, 2005), C58C1(pTiB6S3DT-DNA, pCH32) achieves higher transient transformation efficiency than the wild type C58 virulent strain or the C58-derived disarmed strain GV3101(pMP90) in A. thaliana seedlings (Wu et al, 2014b).…”
Section: Transient Transformation In Seedlingsmentioning
confidence: 78%
“…For transient transformation, T-DNA integration into the host genome is not required, and T-DNA expression usually lasts for a few days (Wroblewski et al, 2005;Marion et al, 2008;Jones et al, 2009;Kim et al, 2009;Li et al, 2009;Tsuda et al, 2012;Wu et al, 2014b). It presents useful advantages, in that it allows results of experimental treatments to be observed in a short period of time, as discussed below.…”
Section: Stable Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthocyanin was measured as previously described with some modifications (Lange et al, 1971;Wu et al, 2014). Arabidopsis seedlings were quickly weighed, boiled for 3 min in extraction solution (propanol:HCl: H 2 O = 18:1:81), and incubated at room temperature in the dark for at least 2 h. Samples were centrifuged, and the absorbance of the supernatants was measured at 535 and 650 nm.…”
Section: Anthocyanin Measurementmentioning
confidence: 99%
“…Arabidopsis transient assays were performed using 5-d-old seedlings infiltrated with Agrobacterium GV3101 carrying pELF3:ELF3:LUC according to a previously described procedure (Wu et al, 2014). Luciferase activity measurements were performed for 36 h with a CCD camera.…”
Section: N Benthamiana and Arabidopsis Transient Transformationmentioning
confidence: 99%